Inhibition of Human Osteoblast Growth by Unfractionated Heparin and by Low Molecular Weight Heparins in vitro - Kock, H. J.; Handschin, A. E. (Thrombosis and Haemostasis, 2002)
Abbreviations: LMWHs: Low molecular weight heparins, UFH: Unfractionated heparin